Analysis of legal framework on investment promotion and contribution to technology dissemination in Tanzania: A case of selected mining companies - Bonephace, Mectrida (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Award of Master of Laws Degree (Commercial Law) of Mzumbe University.